or
Don’t have an account? Sign up
or
Sign up with Google or Facebook
or
By signing up I agree to StudyBlue's
Terms of Use and Privacy Policy
Already have an account? Log in
c=q/m(Δt) OR q=mc(changeint)
*note the lowercase c
where:
q=heat
m=mass
t=temp
Equation for heat capacity:
C=q/(Δt)
*note the uppercase C
where
q=heat
t=temp
1. heat changes measured under constant pressure conditions in a device open to the atmosphere
ΔH= q_{p}
2. heat changes measured under constant volume conditions in a sealed container
ΔE = q_{v}
*E=internal energy
H = E + p V
(enthalpy = internal energy + (pressure x volume))
(mol/liter)/second = mol l^{-1}s^{-1} = Ms^{-1}
Rate of reaction = Δ[reactant] / time interval
OR rate = Δ[reactant] / Δt
* note that t in this case stands for time interval, NOT temperature
Include the stoichiometric coefficients of the reactant if the coefficients do not equal unity.
Rate of substance A = -(1/a)(Δ[A]/Δt)
*t= time interval
*note that we need a negative sign when finding the rate of a reactant
Rate of substance C = (1/c)(Δ[C]/Δt)
*t= time interval
*note that we do NOT need a negative sign when finding the rate of a product
rate = k[reactant]^{n}
*n=determined by experiment
*k=rate constant
If an equation is: aA + bB --> cC + dD, what is the forward rate law?
rate = k[A]^{x}[B]^{Y}
*X and Y are determined through experiment
*k = rate constant
[A]_{t} = [A]_{0} - kt
*[A]_{t} = concentration of A at time t
*[A]_{0} = concentration of A at t=0 (initial concentration of A)
*k = rate constant
*t = time
slope(y) = -k
x = t <-- x-axis
y= [A]_{t }<-- y-axis
b= [A]_{0} <--how far you would move up on the y axis
y = ln([A]_{0}/[A]_{t})
m(slope) = k
x = t
y = 1/[A]_{t}
m(slope) = k
x = t
b = 1/[A]_{0}
t_{1/2} = [A]_{0}/2k
k = Ae^{-Ea/RT}
*E_{a} = Activation Energy
*k = rate constant
*R = gas constant
*T = temp (kelvin)
*A = frequency factor (related to collision frequency)
ln(e) = 1
ln(XY) = ln(X) + ln(Y)
ln(X/Y) = ln(X) - ln(Y)
ln(X^{m}) = m ln(X)
ln(e^{y}) = Y ln(e) = Y
lnk = ln(Ae^{-Ea/RT}) , which is then written as: lnk = lnA - (E_{a}/RT)
y = lnk
m = -(E_{a}/R)
b = lnA
x = T^{-1}
k_{c} = Ae ^{-Ea,c/RT}
k = Ae ^{-Ea/RT}
^{}
Then re-write it all as k_{c}/k = e^{(Ea-Ea,c)/(RT)}
reaction quotient = (concentration of products)^{product coeff.}/ (concentration of reactants)^{reactant coeff.}
OR Q = [products]^{product coeff.}/ [reactants]^{reactant coeff.}
*Q = reaction quotient
What is the reaction quotient for: aA + bB --> cC + dD ?
Q = [C]^{c}[D]^{d}/ [A]^{a}[B]^{b}
equilibrium constant (K)
*equation is the same as the reaction quotient (Q) equation, but Q is replaced with K
Better way to write K:
K = (([C]/M)^{c}([D]/M)^{d}) / (([A]/M)^{a}([B]/M)^{b})
*K is dimentionless!
Plug each into the ideal gas law to make:
P_{A} = [A]RT and P_{B} = [B]RT
Then, plug the results into the expression for K_{p}
n_{A}/V_{B}=[A] and n_{B}/V_{B} = [B]
Then, re-write as K_{p} = [B]^{b}/[A]^{A} x (RT)^{Δn}
where Δn = b-a
therefore, K_{p} = K_{C}(RT)^{Δn}
K_{c} = [CO2]
*Pure solids and liquids do not appear in the final equilibrium constant expression
K_{p} = p_{CO2}
A + B <--> E + F
K_{c} = [E][F]/[A][B]
ax^{2} + bx + c = 0
OR
x = (-b +- (SQ ROOT OF (b^{2} - 4ac)) / 2a
1. Concentration of molarities
2. Change Line
3. Equilibrium Line (molarity + change line)
* reactants on left, products on right
"StudyBlue is great for studying. I love the study guides, flashcards, and quizzes. So extremely helpful for all of my classes!"
Alice, Arizona State University